Cryo‐Immunoelectron Microscopy of Adherent Cells Improved by the Use of Electrospun Cell Culture Substrates. (23rd May 2013) - Schmiedinger, Thomas; Vogel, Georg F.; Eiter, Oliver; Pfaller, Kristian; Kaufmann, Walter A.; Flörl, Angelika; Gutleben, Karin; Schönherr, Sabine; Witting, Barbara; Lechleitner, Thomas W.; Ebner, Hannes‐L.; Seppi, Thomas; et al.
Synopsis Spiderweb‐like gelatine matrices generated by electrospinning are introduced as versatile substrate for culturing animal cell monolayers destined for cryofixation and EM. Thus, non‐disruptive sampling and transfer of native cells into high‐pressure freezing devices is possible within about 30 seconds. In addition to cryosection‐ and replica‐labelling, this aproach can be applied to various complementary microscopy and biochemical methods. <boxed-text content-type="graphic" position="anchor" orientation="portrait"> </boxed-text>